SISTEM DRAINASE ALIRAN BAWAH TANAH UNTUK DAERAH RAWAN LONGSOR (STUDI KASUS SUB DAS SUNGAI CIKAPUNDUNG, BANDUNG) - Endah Lestari (Sekolah Tinggi Teknik - PLN, 2017)
Cikapundung River Restoration lies in a river border with a steep sloping slope and waves to the west - eastwhich is formed from the flow of the river cikapundung. Generally, the soil structure of the CikapundungRiver Basin slope is residual ground, corrosion stone and colluvial deposition,which caused vulnerable tolandslides. It was also separate and able to keep water. Therefore, shear strength is weak, especially if wateris saturated. In this case landslides always occur when it rains. In general, this is due to high rainfall with acertain duration, thus causing the stability of the slope is disrupted. Another cause is the non-functioningdrainage system because it is covered by some material from the slopes submitted by water. Therefore, thewater rubs the slope.